2017
DOI: 10.1088/1361-6560/aa54ef
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intraocular pressure on elastic wave velocity estimates in the crystalline lens

Abstract: Intraocular pressure (IOP) is believed to influence the mechanical properties of ocular tissues including cornea and sclera. The elastic properties of the crystalline lens have been mainly investigated with regard to presbyopia, the age-related loss of accommodation power of the eye. However, the relationship between the elastic properties of the lens and IOP remains to be established. The objective of this study is to measure the elastic wave velocity, which represents the mechanical properties of tissue, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…Further, TM stiffness might be a surrogate marker for conventional outflow pathway function. Novel technologies are being developed to measure ocular tissue stiffness in situ 34 37 , and could thus hold promise for future diagnostic benefit in glaucoma if they could be adapted to the TM.…”
Section: Discussionmentioning
confidence: 99%
“…Further, TM stiffness might be a surrogate marker for conventional outflow pathway function. Novel technologies are being developed to measure ocular tissue stiffness in situ 34 37 , and could thus hold promise for future diagnostic benefit in glaucoma if they could be adapted to the TM.…”
Section: Discussionmentioning
confidence: 99%
“…OCE has been used to evaluate tissue biomechanics 14 and, especially, in ophthalmology. 5 , 6 , 8 , 15 19 Of particular note is dynamic OCE to map corneal elasticity using noncontact mechanical loads based on air-puffs 6 , 8 , 11 , 20 22 or acoustic microtapping ( ). 5 , 15 , 23 …”
Section: Introductionmentioning
confidence: 99%
“… 21 , 24 In our previous work, we have used dynamic OCE and acoustic-based methods for noninvasively assessing lenticular biomechanical properties. 25 29 We have demonstrated that the biomechanical properties of the crystalline lens can be measured in situ and quantified variations in the stiffness of mammalian lenses as a function of age and intraocular pressure. 25 , 27 29 Shear wave elastography is one of the most common elastography techniques because it does not need a priori information about the sample or excitation, and it can be performed completely noninvasively.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Ultrasound-based shear wave elastography techniques have been used to evaluate the biomechanical properties of various animal lenses. 25 , 31 , 32 However, the low resolution, poor contrast, and large excitation forces of ultrasound-based techniques may not be suitable for in vivo applications. Thus, we propose the use of OCE to detect elastic waves in the lens to characterize lenticular biomechanical properties.…”
Section: Introductionmentioning
confidence: 99%